Lignocellulosic Bioethanol Production of Napier Grass Using Trichoderma reesei and Saccharomyces cerevisiae Co-Culture Fermentation - Mueansichai, Thirawat; Rangseesuriyachai, Thaneeya; Thongchul, Nuttha; Assabumrungrat, Suttichai (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Bioethanol from agricultural waste is an attractive way to turn waste into added value that will solve the problem of food competition and waste management. Napier grass is a highly productive and effective lignocellulosic biomass, which is an important substrate of the second-generation biofuels. In addition, several processes are required in the production of ethanol from lignocellulosic materials; thus, co-culture fermentation can shorten the production process. This experimental research utilizes Trichoderma reesei and Saccharomyces cerevisiae co-culture fermentation in the bioethanol production of Napier grass using simultaneous saccharification and fermentation technology. To improve ethanol yield, Napier grass was pretreated with 3% (w/w) sodium hydroxide. An orthogonal experimental design was employed to optimize the Napier grass content, mixed crude co-culture loading, and incubation time for maximum bioethanol production. The results showed that pretreatment increased cellulose contents from 52.85% to 82%. The optimal fermentation condition was 15 g Napier grass, 15 g mixed crude co-culture, and 7 days incubation time, which maximizes the bioethanol yield of 16.90 g/L. Furthermore, the fermentation was upscaled 20-fold, and experiments were performed with and without supplemented sugar using laboratory-scale optimal fermentation conditions. The novelty of this research lies in the use of a mixed crude co-culture of T. reesei and S. cerevisiae to produce bioethanol from Napier grass with the maximum bioethanol concentration of 25.02 and 33.24 g/L under unadded and added sugar conditions and to reduce operational step and capital costs.